The role of Bhabinkatibmas in tackling criminal acts of theft at the Garut Police - Tegu, Florentinus Jati Pranowo (Police Studies Review, 2024)
Indonesia is being faced by transportation problems which are increasing in line with the increasing number of existing people and the enactment of regional autonomy affects the economic level of each region differently so that there will be an increasing unemployment rate and the potential of Curanmor itself, so that the role of Bhabinkamtibmas is needed to overcome it. The author proposes four problems in this thesis, namely about; (1) How is the modus operandi of criminal acts of Curanmor (2) How is the implementation of the role of Bahbinkamtibmas in dealing with criminal acts of Curanmor (3) What are the efforts made by Bhabinkamtibmas (4) What are the obstacles faced by Bhabinkamtibmas in dealing with Curanmor Criminal Acts. In analyzing these problems, researchers used the field and research method with a qualitative approach, with data collection techniques: observation, interview and document inspection. Theories and concepts that the author uses in this research are management theory, role theory, communication theory, bhabinkamtibmas concept, promoter concept and community policing concept. Data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of this study and conclusions of this study show that (1) The modus operandi of the crime of fraud itself that often occurs is by using the T key and or damaging the key (2) The role of the bhabinkamtibmas carried out in Garut District Police include home visits and giving guidance and guidance to the community and the community but this role is not yet optimal. (3) Activities carried out at Garut Regional Police Station, namely door to door sambaing, anjangsana and FKPM formation. (3) Constraints that affect include the lack of personnel, facilities and infrastructure used, personnel motivation, cultural culture and the lack of understanding of the Garut community towards the concept of bhabinkamtibmas. From the findings of the study, the authors suggest that the Chief of Garut District Police be serious in facing the problem of Curanmor since the adoption of this Criminal Act is very high every year and instructs Bhabinkamtibmas to be more intensive in carrying out its duties.